Time-Resolved Energy Dispersive EXAFS Measurement of Oligomerization Reaction Catalyzed by Nickel Homogeneous Catalyst on Addition of Triphenylphosphine and AlEt2(OEt) as Co-Catalyst - Abdul Rahman, M.B.; Evans, J.; Dent, A.J. (Asian Journal of Chemistry, 2010)
Energy dispersive EXAFS (EDE) data have been analysed for the nickel (3-diketonate catalysts. Ni( dpm)2, using curved wave theory with ab initio phase shifts. The derived parameters for metal compounds were in good agreement, within experimental error of 0.02-0.05 Å for the bond distances. Time-resolved EDE studies on Ni(dpm)2 : PPh3 : AlEt2(OEt) : 1-hexene of 1: 2 : 4 : 20 were acquired within 0.24 s for each spectrum. The growth of a pre-edge feature and change at the top of the edge can be clearly seen to show that the reaction reached completion in less than 6 s. A stopped flow system was used for in situ time-resolved EDE studies on the nickel systems at room temperature. EDE measurements using a new rectangular Si(IlI) monochromator and Hamamatsu S4874 photodiode array at Station 9.3, Daresbury Laboratory have yielded consecutive spectral data taken at 1-1000 accumulations with 2-30 ms integration time to follow the changes during initiation of the catalytic reaction.